Verbal Semantics And Differential Object Marking In Lycopolitan Coptic - Engsheden, Åke (My University, 2018)
This paper seeks to clarify the role of affectedness for the marking of direct objects through an analysis of a corpus of Lycopolitan Coptic texts (4th to 5th centuries AD). Whereas previous research has shown the importance of definiteness for the use of the direct object marker n with the so-called imperfective tenses (present and imperfect), it has proven more difficult to establish why it alternates in the non-imperfective with a zero marker. An attempt is made here to correlate the two different object constructions to Tsunoda’s verb-type hierarchy, which was conceived to capture the degree of affectedness. It appears that the more affected a direct object is, the more likely it is to receive the direct object marker; whenever the object is little affected or unaffected, the zero-marked construction is preferred.
Keywords: Historical grammar; Differential Object Marking; Lycopolitan Coptic